Highly oriented GeSe2 thin film growth using a facile low-vacuum annealing method. (June 2021) - Nguyen, Phuong; Nguyen, Anh Duc; Cho, Sunglae
Abstract: Germanium diselenide (GeSe2 ), a chalcogen-based wide-bandgap semiconductor, has recently attracted interest as a low-symmetry layered material with peculiar in-plane anisotropy. The excellent air stability of ultra-thin GeSe2 flakes and impressive preliminary results for photodetection-based applications in the ultra-violet light region also make a new promising material in the field of optoelectronics. The throughput of thin GeSe2 crystal production on compatible substrates, however, has been extremely low, and accordingly, an improvement is essential. Herein, we report the preparation of crystalline GeSe2 thin films from non-crystalline continuous films of a Ge-Se mixture deposited on a-SiO2 /Si substrates, and the crystal structure of the post-annealed thin films characterized by X-ray crystallography. Well-oriented crystalline grains with lateral sizes up to 50 µm were observed after an appropriate annealing procedure. This self-aligned growth could establish a facile approach for scaling-up production of oriented crystalline thin films of other Van der Waals layered materials besides GeSe2 . Graphical abstract: Image, graphical abstract